Testosterone measurements in early infancy. Issue 6 (21st October 2004) - Tomlinson, C; Macintyre, H; Dorrian, C A; Ahmed, S F; Wallace, A M
Abstract : Circulating testosterone concentrations in infants measured by a direct chemiluminescent immunoassay (Bayer ADVIA Centaur) were compared with those measured by a traditional radioimmunoassay using solvent extraction. The results confirm that neonatal circulating testosterone concentrations are method dependent, and each laboratory should establish method related reference ranges especially if using a direct commercial immunoassay. The results indicate that the Bayer ADVIA Centaur procedure can be used reliably in neonates. Expected values for male and female infants < 10 days old were 2.5–11.1 (n  =  36) and 1.7–5.6 (n  =  36) nmol/l respectively. For older neonates (10–50 days) the ranges were 0.2–17.2 (n  =  42) and 0.1–1.5 (n  =  7) nmol/l respectively.